(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes financing strategies for “greenfield” mining projects in the context of the Russian economy. Two main financing models are considered: full financing through own funds and project financing which is a combination of own funds financing and bank’s project lending with limited recourse to the project’s sponsor. The focus is on comparing financial indicators such as capital cost, internal rate of return (IRR), return on investment (ROI), and payback period. Key risks, including economic, geological, technological, and political factors, are assessed. The influence of international conditions, regulatory changes, and sustainable development policies on companies’ financial strategies is also examined. The article provides practical recommendations for optimizing capital structure and selecting the most effective financing model for the mining industry